Reducing Otitis Media Recurrence Through Nurse, Pharmacist, Public Health Education and Follow Up - Hussain Ali Alzaid⁷, Ahmed Hussain Alsaleh⁸, Kawther Mohammed Al Khalaf⁹, Mohammed Ahmed Alshayeb¹⁰, Hussain Abdulhadi Alsidran¹¹, Sajedh Mohammed Alturaiki¹², Mohammed Dawood Alkhalaf¹, Ahmed Abdulmohsen Alhamoud², Abdulmohsen Abdullah Alabdulaziz³, Zahrah Hussin Ali Buhasson⁴, Abdulmonem Ali Albarakat⁵, Mohammed Jawad Alabed⁶ (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Otitis media (OM) is a common childhood infection characterized by inflammation of the middle ear. Recurrent otitis media (ROM) poses significant challenges, often leading to complications, antibiotic resistance, and the need for surgical interventions. This review explores the potential for reducing OM recurrence through coordinated efforts of nurses, pharmacists, and public health professionals in patient education and follow-up. Key strategies include educating families on risk factors, promoting breastfeeding and pneumococcal vaccination, ensuring proper antibiotic administration and adherence, and identifying and managing allergies and upper respiratory infections. School-based screening programs can aid in early detection and referral. Pharmacists play a vital role in promoting judicious antibiotic use and providing guidance on symptomatic management. Public health initiatives focusing on reducing exposure to environmental tobacco smoke, improving hygiene practices, and addressing socioeconomic disparities are crucial. Implementing standardized follow-up protocols and leveraging electronic health records and patient registries can help track outcomes and target interventions. Multidisciplinary collaboration, parental engagement, and culturally sensitive approaches are essential for effective prevention and management of ROM.